Student engagement in higher education theoretical perspectives and practical approaches for diverse populations - Quaye, Stephen John 1980-; Harper, Shaun R. 1975-; Pendakur, Sumun L. (Routledge, 2020)
"In the updated edition of this important volume, the editors and chapter contributors explore how diverse populations of students experience college differently and encounter group-specific barriers to success. Informed by relevant theories, each chapter focuses on engaging a different student population, including low-income students, students of color, international students, students with disabilities, religious minority students, student-athletes, part-time students, adult learners, military-connected students, graduate students, and others. New in this 3rd edition is the inclusion of chapters on Indigenous students, student activists, transracial Asian American adoptee students, justice-involved students, student-parents, first generation students, and undocumented students. The forward-thinking, practical, anti-deficit-oriented strategies offered throughout the book are based on research and the collected professional wisdom of experienced educators and scholars at a range of postsecondary institutions. Current and future faculty members, higher education administrators, and student affairs educators will undoubtedly find this book complete with fresh ideas to reverse troubling engagement trends among various college student populations"--